A Comparative Analysis of Misery Index and Its Impact on Health Indicators Across The Globe - Aishwarya; Rajmohan; Suganya.P; Prabu.D; Bharathwaj; M.R.Prashanthy (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: This study aims to analyze the impact/relationship of the health indicators and the human developmentindex over the globe’s misery index.Materials and Method: In this paper, a comparative data analysis of the misery index, health indicators likemortality rate, disability rate, Quality of life index, and human development index, along with the rankingbased on the human development index, were done by tabulating the data collected from the electronicsources.Results: There was a strong correlation between the misery index, human development index, and healthindicators.Conclusion: This paper clearly shows that the misery index of a country was highly influenced by the healthindicators, such as the mortality rate, disability rate, and Quality of life. Further, the human developmentindex also had a comparative impact on the misery index of a country. Hence, this study depicted a descriptivestatistical relationship among the misery index, the health indicators (mortality rate, disability rate, Qualityof life) and the Human Development Index (HDI).